2013
DOI: 10.1063/1.4830259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-temperature (77 K) quasihydrostatic extrusion on the properties of high-purity titanium: The role of initial structural state

Abstract: This is a study of the effect of quasihydrostatic extrusion at liquid nitrogen and room temperatures on the evolution of the structure and mechanical properties of high-purity titanium produced by severe plastic deformation in a swaging-extrusion-drawing regime and with subsequent annealing at temperatures of 350–550 °C. It is shown that a combination of severe plastic deformation and cryogenic quasihydrostatic extrusion makes it possible to create high-purity nanocrystalline titanium with high strength and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This may mean that the grain size is not the only parameter that determines the value of Δ. In [16] it was shown that despite the fact, that the quasihydrostatic extrusion of SPD samples at 300 K (SPD+QHE300) results in some grain refinement (130 nm as compared to 150 nm for the SPD samples), the yield strength σ0.2t decreases. It was suggested that one of the reasons for this anomalous effect could be a change in the stressed state and density of dislocations.…”
Section: Eejp 3 (2019)mentioning
confidence: 99%
See 1 more Smart Citation
“…This may mean that the grain size is not the only parameter that determines the value of Δ. In [16] it was shown that despite the fact, that the quasihydrostatic extrusion of SPD samples at 300 K (SPD+QHE300) results in some grain refinement (130 nm as compared to 150 nm for the SPD samples), the yield strength σ0.2t decreases. It was suggested that one of the reasons for this anomalous effect could be a change in the stressed state and density of dislocations.…”
Section: Eejp 3 (2019)mentioning
confidence: 99%
“…This strength is conditioned by small grain size, high uniformity of the grain structure and presence of highangle boundaries. In [16] the role of the initial grain size of high-purity titanium samples, obtained by the SPD method and subsequent annealing, was studied in the evolution of their structure and variation of their properties under the impact of CD by the quasi-hydrostatic extrusion (QHE) method at liquid nitrogen temperature. Such a low-temperature deformation resulted in grains refinement in the high-purity sub-microcrystalline titanium up to nanolevel, i.e.…”
mentioning
confidence: 99%
“…In addition to using separate pressure treatment methods, an effective technique for structure dispersion is the combination of various methods, which are characterized by different stress diagrams. In particular, it was shown in [8] that the combination of severe plastic deformation according to the upsetting-extrusiondrawing scheme with cryogenic quasi-hydroextrusion (QHE) made it possible to create nanocrystalline titanium (grain size 75 nm) of increased purity with high mechanical properties (ultimate strength σ В = 930 MPa, plasticity  ≈ 12%).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods (or techniques) were harnessed to produce ultrafine-grained/nanostructured titanium. These techniques of processing titanium can be classified into Basic SPD Processing that includes ECAP [5,817,2032], Accumulative Roll-Bonding [3337], High Pressure Torsion (HPT) [28,3858], and Torsion Extrusion [5961], Conventional Metal Forming-Based Processing including Hydrostatic Extrusion [27,62…”
Section: Introductionmentioning
confidence: 99%